Good morning, Mr Mandela - La Grange, Zelda (New York, New York : Viking, 2014)
One of Mandela's three private secretaries and now working for the Nelson Mandela Foundation, "La Grange pays tribute to Nelson Mandela as she knew him: a teacher who gave her the most valuable lessons of her life. The Mr. Mandela we meet in these pages is a man who refused to be defined by his past, who forgave and respected all, but who was also frank, teasing, and direct. As he renewed his country, he also freed La Grange from a closed world of fear and mistrust, giving her life true meaning"--Amazon.com.
Prologue : Zeldina -- Part 1. 'If it isn't good, let it die,' 1970-1994. Childhood -- Change -- Part 2. Start of a new dawn, 1994-1999. Meeting Mr Mandela -- Working for a president -- Travelling with a president -- Running to keep up -- Part 3. Gatekeeper to the most famous man in the world, 1999-2008. Travel and conflict -- Working with world leaders -- Holidays and friends -- The biggest fundraiser of my life -- Part 4. What next? 2009-2013. Staying until the end -- Saying goodbye -- Tot weersiens Khulu!
"A memoir"--Dust jacket.
Keywords: La Grange, Zelda -- Friends and associates; La Grange, Zelda -- Political and social views; Mandela, Nelson, -- 1918-2013.; Mandela, Nelson, -- 1918-2013 -- Friends and associates; Private secretaries -- South Africa -- Biography; South Africa -- Politics and government -- 1994-; South Africa -- Social conditions -- 1994-